Implementasi port knocking dinamis berbasis waktu pada router untuk pengamanan akses SSH - junga, David; Sulistyo, Wiwin (IT Explore: Jurnal Penerapan Teknologi Informasi dan Komunikasi, 2025)
This research proposes a time-based dynamic port knocking technique on Mikrotik routers to enhance SSH access security. The system uses an algorithm for port calculation that changes according to the server’s time, requiring a different knocking sequence for each access session. The technique involves three consecutive knocking stages, where each stage must be passed in order for SSH access to be granted. The results show that this method is effective as a two-factor authentication mechanism, limiting access only to clients who understand the port calculation algorithm. Moreover, this system helps prevent brute-force attacks more efficiently by changing the port every minute, making it more difficult for unauthorized parties to launch an attack. Therefore, this method offers a more dynamic, adaptive, and flexible SSH security solution that can effectively address modern cybersecurity threats.